Simultaneous and sequential choice as a function of reward delay and magnitude: normative, descriptive and process-based models tested in the European starling (Sturnus vulgaris). - Shapiro, MS; Siller, S; Kacelnik, A (2008)
The authors analyze prevalent theoretical and empirical quantitative models of choice using data from European starlings (Sturnus vulgaris). The different models originate from diverse lines of thinking, including optimal foraging theory, descriptive behavioral analysis, and temporal discounting. The authors also investigate the Sequential Choice Model (SCM) that predicts choice between simultaneous alternatives as a function of behavior in sequential encounters. SCM assumes that simultaneous encounters are rare in nature, where animals often exploit or dismiss single opportunities. Mechanisms of choice adapted for sequential encounters may be evolutionarily stable even if they impose a cost in the rarer simultaneous cases. The best predictive power is achieved by the SCM and by hyperbolic discounting with value (or attractiveness) of each option proportional to reward amount and inversely proportional to the sum of delay to reward plus delay to respond. Choice probability matched the ratio of each option's value to the sum of values of all available options. The good fit of SCM supports the view that choice is driven by mechanisms adapted to sequential, rather than simultaneous encounters with feeding opportunities.